Risk Factors of Primary Postpartum Hemorrhage in Siriraj Hospital - Tripop Lertbunnaphong; Jarunee Leetheeragul; Wiboolphan Thitadilok (Siriraj Medical Journal, 2020)
Objective: To explore the risk factors of primary postpartum hemorrhage (PPH) in pregnant women who delivered at Siriraj Hospital.